A Scheme for Financial Assistance: The League of Nations’ Attempt at Maintaining World Peace - Peschcke-Køedt, Nils Andreas Holm (Culture and History: Student Research Papers, 2023)
This article studies how the League of Nations sought to create an international security framework of financial assistance from 1925 to 1930. By analyzing the internal files of the League of Nation’s archives, it provides an inside-out institutional analysis of the League’s Economic and Financial Organization and shows how key League and non-League actors with idealistic notions of the Convention’s ‘swiftness’ and ‘sureness’ bridged concerns of legal legitimacy. While earlier writing on the League has focused on the failure of its peacekeeping ambition, this article shows how it was pursued and argues that the Convention was conceived in a nexus of optimistic, liberal, and technocratic ideas of the global market’s deterrence potential.